Screening for the Detection of IgG anti-Toxoplasma gondii Antibodies in Female Donors at Semarang Regency - Afrianti, Dina; Putri, Adita Puspitasari Swastya; Wikandari, Ririh Jatmi; Wahyudi, Wahyudi (Poltekkes Kemenkes Palu, 2024)
Toxoplasmosis is a widespread zoonotic disease caused by Toxoplasma gondii (T.gondii). Blood and blood products are possible routes of transmission of T. gondii, especially in patients who have undergone multiple transfusions. The aim of this study is to determine the seroprevalence of toxoplasmosis in female donors using blood serum which is analyzed serologically to detect ImmunoglobulinG (IgG) using the Enzyme-Linked Fluorescent Assay (ELFA) method, as well as the relationship between risk factors for toxoplasmosis, such as keeping cats, receiving blood transfusions, eating undercooked meat and eating raw vegetables. This research is an analytic observational study using a cross-sectional study design. The sample taken is female donor candidates who are willing to participate during the study period, from March to September 2023, and have met the inclusion criteria to become research subjects by explaining the purpose and procedure of the study and the consent letter signed by each research subject before blood samples were taken and filling out the research questionnaire. 177 blood serum samples of female donors were collected from blood donor candidates using consecutive sampling method and a questionnaire to obtain risk factor data that influence the incidence of toxoplasmosis. The results showed that the seroprevalence of toxoplasmosis in the blood of female donor at Indonesian Red Cross Blood Donor Unit (UDD PMI) Semarang Regency, Central Java Province was 26.6%. In this study the risk factors that influence the incidence of toxoplasmosis are consuming raw vegetables with 5.835 times more risk than women who do not consume raw vegetables, while other factors such as keeping cats, receiving blood transfusions, and eating undercooked meat, have no significant effect. The seroprevalence of toxoplasmosis in female donors at UDD PMI of Semarang Regency is quite high due to the habit of eating raw vegetables or fresh vegetables with a very high transmission potential.